La Directive 2010/63/UE – un tournant pour la primatologie ? - Christophe Joubert (Revue de Primatologie)
After 10 years of debate and controversy, the regulations on the use of animals for scientific purposes will change with the replacement of Directive 86/609/EEC by Directive 2010/63/UE. The new Directive sets up new more stringent requirements for the use of animals in biomedical research with the aim to improve their protection. These provisions are supplemented by specific measures concerning the use of nonhuman primates (NHP). The benefits and improvements for NHP in terms of well-being and conditions of use will be significant and the ethical approach related to the use of experimental animals will develop. However, these provisions will also result in increased constraints for research. The uncertainties on the final balance between the "profit" for the protection of animals and the "cost" for research are important and raise questions about the future of primatology in France.